Maternal factors associated with hyperglycemia in pregnancy and perinatal outcomes: A Brazilian reference center cohort study - Nicolosi, Bianca F. [UNESP]; Vernini, Joice M. [UNESP]; Costa, Roberto A. [UNESP]; Magalhães, Claudia G. [UNESP]; Rudge, Marilza V. C. [UNESP]; Corrente, José E. [UNESP]; Cecatti, Jose G.; Calderon, Iracema M. P. [UNESP] (Springer Nature, 2020)
Background: While sufficient evidence supporting universal screening is not available, it is justifiable to look for specific risk factors for gestational diabetes mellitus (GDM) or hyperglycemia in pregnancy (HIP). The objective of this study is to identify independent risk factors for HIP and its adverse perinatal outcomes in a Brazilian public referral center. Methods: We included 569 singleton pregnant women who were split into three groups by glucose status: GDM (n = 207), mild gestational hyperglycemia (MGH; n = 133), and control (n = 229). Women who used corticosteroids or had a history of DM were excluded. HIP comprised both GDM and MGH, diagnosed by a 100 g- or 75 g-oral glucose tolerance test (OGTT) and a glucose profile at 24-28 weeks. Maternal characteristics were tested for their ability to predict HIP and its outcomes. Bivariate analysis (RR; 95% CI) was used to identify potential associations. Logistic regression (RRadj; 95% CI) was used to confirm the independent risk factors for HIP and its perinatal outcomes (p < 0.05). Results: Age ≥ 25 years [1.83, 1.12-2.99], prepregnancy BMI ≥ 25 kg/m2 [2.88, 1.89-4.39], family history of DM [2.12, 1.42-3.17] and multiparity [2.07, 1.27-3.37] were independent risk factors for HIP. Family history of DM [169, 1.16-2.16] and hypertension [2.00, 1.36-2.98] were independent risk factors for C-section. HbA1c ≥ 6.0% at birth was an independent risk factor for LGA [1.99, 1.05-3.80], macrosomia [2.43, 1.27-4.63], and birthweight Z-score > 2.0 [4.17, 1.57-11.10]. Conclusions: MGH presents adverse pregnancy outcomes similar to those observed in the GDM group but distinct from those observed in the control (no diabetes) group. In our cohort, age ≥ 25 years, prepregnancy BMI ≥ 25 kg/m2, family history of DM, and multiparity were independent risk factors for HIP, supporting the use of selective screening for this condition. These results should be validated in populations with similar characteristics in Brazil or other low- and middle-income countries.
Keywords: Gestational diabetes; Hyperglycemia; Perinatal outcomes; Pregnancy; Risk